Women, writing and the Iraqi Baʻthist State : contending discourses of resistance and collaboration, 1968-2003 - Al-Hassan, Hawraa (Edinburgh studies in modern Arabic literature., 2020)
Explores discourses on gender and representations of women in modern Iraqi fiction. By exploring discourses on gender in both propaganda and high art fictional writings by Iraqis, this book offers an alternative narrative of the literary and cultural history of Iraq.